INOVASI PENGEMBANGAN BAURAN PEMASARAN DI CV BONEE ENGGENERING BANDUNG JAWA BARAT - andi, Andi; Supriyoso, Patria (JEBIM Prima, 2024)
Challenges faced by businesses in the era of open competition in Industry 4.0 must be anticipated accurately. Entrepreneurs are required to be creative, adaptive, and astute in addressing this phenomenon. They must be able to withstand shocks and grow stronger. The author chose the title